1996
DOI: 10.1007/bf01709558
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic trial of diazepam versus placebo in acute chloroquine intoxications of moderate gravity

Abstract: Diazepam, at the dose studied, does not appear to reverse the chloroquine-induced membrane-stabilising effect in acute moderately severe chloroquine intoxication. Supportive intensive care of these intoxications appears to be all that is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…Chloroquine and hydroxychloroquine are dangerous in overdose [47,93,[109][110][111][112][113][114][115][116]. In selfpoisoning, nausea, vomiting, diplopia, hypoacusis, and dysphoria are sometimes followed by tremors, athetoid movements, dysarthria, difficulty swallowing, lethargy and drowsiness, and then seizures, coma, hypotension, hypokalaemia, arrhythmias, and ventricular fibrillation.…”
Section: Chloroquine Poisoningmentioning
confidence: 99%
See 1 more Smart Citation
“…Chloroquine and hydroxychloroquine are dangerous in overdose [47,93,[109][110][111][112][113][114][115][116]. In selfpoisoning, nausea, vomiting, diplopia, hypoacusis, and dysphoria are sometimes followed by tremors, athetoid movements, dysarthria, difficulty swallowing, lethargy and drowsiness, and then seizures, coma, hypotension, hypokalaemia, arrhythmias, and ventricular fibrillation.…”
Section: Chloroquine Poisoningmentioning
confidence: 99%
“…Hypokalaemia, resulting from intracellular accumulation, is an important complication, an indicator of prognosis, and a contributor to arrhythmias [93]. It has been suggested that diazepam is a specific antidote [109] for chloroquine poisoning, but more recent studies do not support a specific role for this drug above good haemodynamic and ventilatory support [111,112]. There is a loose relationship between the self-administered chloroquine dose and the resulting blood concentrations.…”
Section: Chloroquine Poisoningmentioning
confidence: 99%
“…Il s'agit de l'apparition d'une oligurie, l'élévation de la créatinémie, la persistance ou l'augmentation d'une hyperlactacidémie, en sachant que sa valeur initiale n'a pas de valeur pronostique et de l'augmentation de la chloroquinémie ( ≥ 20 % dans les six heures). Il est prudent d'admettre en réanimation toute intoxication aiguë à la chloroquine, mais il est inutile de distinguer les formes mineures et modérées, car il n'en résulte pas de différence de prise en charge [26]. La surveillance rapprochée de ces patients permet de dépister tout facteur de pronostic péjoratif, impliquant la mise en route du traitement maximaliste.…”
Section: La Chloroquineunclassified
“…Subsequent case reports (Jaeger, Sauder, Kopferschmitt, & Flesch, 1987;Meeran & Jacobs, 1993;Rajah, 1990) and a prospective non-randomised trial (Riou, Barriot, Rimailho, & Baud, 1988), in which the odds of survival significantly favoured diazepam therapy, led to the recommendation of diazepam in the management of acute chloroquine toxicity. However, there remains controversy given some conflicting evidence of benefit (Demaziere et al, 1992;Clemessy et al, 1996) and limitations in study designs (Yanturali, 2004).…”
Section: Introductionmentioning
confidence: 99%